(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
The blockchain technology that underpins Bitcoin has lately gained a lot of traction. Blockchain is a decentralized transaction ledger that is immutable. Blockchain applications are emerging in a variety of fields, including financial services, reputation systems, and the Internet of Things (IoT), among others. Nonetheless, concerns with blockchain knowledge, like as security or scalability, have yet to be solved. Bitcoin can only process 7 transactions per second, making it unsuitable for high frequency trading. Larger blocks, on the other hand, imply more storage capacity and less network transfer. Because fewer individuals desire to own such a large blockchain, this will ultimately lead to centralization. This article provides a comprehensive description of blockchain technology. The researcher first provides an overview of blockchain architecture and then compares many commonly utilized consensus algorithms in different blockchains. A brief summary of technical difficulties and current advances is also included. They also highlight possible future blockchain developments.